Pengaruh Aktivitas Menghafal Al-Qur’an Terhadap Kecerdasan Spiritual Siswa Madrasah Tsanawiyah Daarussalaam Sukabumi - Subhan Masud; Laila Nurmilah; Neng Syifa Masnoneh; Sifa Fauziah (TA'DIB: Jurnal Pendidikan Agama Islam, 2023)
This study examines the influence of Quran memorization activities on the spiritual intelligence of MTs Daarussalaam Sukabumi students. Basically, a spiritually intelligent person is one who is able to actualize divine values as manifestations in his activities in daily life and strives to maintain harmony and harmony with his nature as a being who depends on the power of the Supreme Creator. One way that can be done to improve spiritual intelligence is to memorize the Quran. The activity of memorizing the Quran has been carried out for quite a long time MTs Daarussalaam Sukabumi. The method used in this study is quantitative research, namely research methods based on positivistic (concrete data), research data in the form of numbers to be measured using statistics as a calculation test tool, related to the problem studied to produce a conclusion. The results of the analysis of the correlation calculation between Qur'an memorization activities and students' Spiritual Intelligence obtained a correlation coefficient value = 0.89. This value gives an understanding that the relationship between Qur'an memorization activities and students' Spiritual Intelligence is very strong (89%) and positive means that the higher the level of Qur'an memorization activity, the lower the student's Spiritual Intelligence. Vice versa, the lower the level of Qur'an memorization activity, the higher the student's Spiritual Intelligence ????????????